ASSESSMENT OF STUDENT PROGRESS AND ACHIEVEMENTS: THE ANALYSIS OF THE FUTURE MUSIC PEDAGOGUES’ APPROACH - Kriščiūnaitė, Asta; Strakšienė, Diana (Acta Paedagogica Vilnensia, 2014)
The article deals with the approach of future music pedagogues towards the assessment of the student progress and achievement in the contemporary process of musical education. The main focus is on the mark as having a metaphysical effect on the student, and a successful music lesson. The research enabled to indicate that future music pedagogues evaluate the assessment of the student progress and achievement as one of the key components in the educational process, as well as the means that enable to evaluate the student’s knowledge, encouraging the competition among students, forming the teacher’s authority, making influence on the inherent features of a student, adjusting the pace of learning / teaching, its content, class discipline, and preserving the status of the school. Such approach does not correspond to the aims of educational process based on the contemporary ideas and adversely affects the aim of the Lithuanian education system to be reoriented to the more attractive contemporary education models which help to foster the student’s emotional awareness, critical approach, free choice, creativity, suitable moral attitudes, etc.
Keywords: assessment of student progress and achievement; musical education; music teachers training